Assessing Cu2L2X4 dimeric moieties as ferromagnetic building blocks in double halide-bridged polymers (X = Cl−, Br− and L = benzamide). An experimental and computational study. (15th July 2020) - Coetzee, Stefan; Turnbull, Mark M.; Landee, Christopher P.; Novoa, Juan J.; Deumal, Mercè; Vela, Sergi; Rademeyer, Melanie
Graphical abstract: Stacked Cu2 L2 X4 dimers, with L = benzamide and X = Cl −, Br −, were synthesized, structurally and magnetically characterized and computationally rationalized, and found to have a complex magnetic topology with potential for tunable magnetic properties. Abstract: Two isostructural double halide-bridged polymers, consisting of stacked Cu2 L2 X4 dimers, with L = benzamide (BA) and X = Cl − in CuClBA and X = Br − in CuBrBA, were synthesised. The experimental magnetic data of both compounds were recorded and it was found that the χ m data fitted a 1D alternating FM/AFM model. A computational First-Principles Bottom-Up computational study was conducted to understand the micro- and bulk magnetic properties. It was determined that a strong ferromagnetic (FM) interaction occurs within the Cu2 BA2 X4 dimer, with an anti-ferromagnetic (AFM) interaction diagonally connecting Cu2 BA2 X4 dimeric moieties. For CuClBA, a 1D alternating FM/AFM chain topology was found, whereas CuBrBA shows additional competing interactions within the 1D alternating FM/AFM chain. Strikingly, the magnetic topology for both compounds is different than that expected from crystal packing analyses. Tuning the weaker competing interactions within the double halide-bridged chains might be a good strategy to extend the bulk FM character of the compound.